Consistent Estimation of Certain Parameters in the Unobservable Variable Model When There is Specification Error - Attfield, Clifford L. F. (The Review of Economics and Statistics, 1983)
Beach, Charles M., and James G. MacKinnon, Maximum Likelihood Procedure for Regression with Autocorrelated Errors, Econometrica 46 (1978), 51-58. Box, G. E. P., and D. R. Cox, An Analysis of Transformations, Journal of the Royal Statistical Society 26, Series B (1964), 211-243. Hall, Bronwyn H., and Robert E. Hall, Time-Series Processor Version 3.5 User's Manual, mimeographed, Stanford, California, 1980. Savin, N. E., and K. J. White, Estimation and Testing for Functional Form and Autocorrelation: A Simultaneous Approach, Journal of Econometrics 8 (1978), 1-12. Spitzer, John J., Primer on Box-Cox Estimation, this REVIEW 64 (May 1982), 307-313. Zarembka, Paul, Transformation of Variables in Econometrics, in Paul Zarembka (ed.), Frontiers in Econ?ometric.s (New York: Academic Press, 1974).